Implementation of REACH in a metalworking industry: a perspective from a downstream user - Coelho, Maria João (2021)
Reach is a European Union's regulation regarding the Registration, Evaluation, Authorisation and Restriction of Chemicals. Reach purpose is the improvement of environmental and human health protection, against riks originated by chemicals.